Design of a Ladder Frame Chassis Made from Aluminum Alloy Hollow Material Used by the GARNESA Energy-Efficient Car Team with Static Testing - Baihaqi, Muhammad Baihaqi Nur; Firman Yasa Utama (Fakultas Teknik Universitas Negeri Surabaya, 2025)
This study focuses on designing a ladder frame chassis for energy-efficient cars made of Hollow Aluminum Alloy. The chassis functions as the main supporting structure that must be able to withstand vehicle loads effectively, including static loads from the steering, driver, engine, and battery, as well as dynamic loads that arise while driving. The design process involves an in-depth analysis of the dimensions and strength of the material to achieve a stable, minimalist, and aerodynamic design. Testing is carried out to evaluate the strength of the chassis through static test methods. The method used is an experimental method where the work on the tool starts from the design which includes: observation, tool design and function testing. The results of the chassis design have final dimensions of 1740.40 mm (length) x 780 mm (width) x 876.20 mm (height), while the results of static testing obtained the highest deflection results of 0.2 cm with a safety factor of 7.29 ul, for the moment of inertia obtained a value of 996730.62 mm4, and for von mises stress 37.77 Mpa. These findings indicate that the designed chassis meets the safety and performance criteria required for energy-efficient cars, so it can be implemented in KMHE and SEM competitions. Keyword: Chassis Ladder Frame, Energy Efficient Car, Urban Concept, Static Test.